Differences of respiratory kinematics in female and male singers – A comparative study using dynamic magnetic resonance imaging - Traser, Louisa; Schwab, Carmen; Burk, Fabian; Özen, Ali Caglar; Bock, Michael; Richter, Bernhard; Echternach, Matthias (Frontiers in Psychology, 2022)
Breath control is an important factor for singing voice production, but pedagogic descriptions of how a beneficial movement pattern should be performed vary widely and the underlying physiological processes are not understood in detail. Differences in respiratory movements during singing might be related to the sex of the singer. To study sex-related differences in respiratory kinematics during phonation, 12 singers (6 male and 6 female) trained in the Western classical singing tradition were imaged with dynamic magnetic resonance imaging. Singers were asked to sustain phonation at 5 different pitches and loudness conditions, and cross-sectional images of the lung were acquired. In each dynamic image frame the distances between anatomical landmarks were measured to quantify the movements of the respiratory apparatus. No major difference between male and female singers was found for the general respiratory kinematics of the thorax and the diaphragm during sustained phonation. However when compared to sole breathing, male singers significantly increased their thoracic movements for singing. This behavior could not be observed in female singers. The presented data support the hypothesis that professional singers follow sex-specific breathing strategies. This finding may be important in a pedagogical context where the biological sex of singer and student differ and should be further investigated in a larger cohort.